2018
DOI: 10.5435/jaaos-d-16-00649
|View full text |Cite
|
Sign up to set email alerts
|

Bony Reconstruction of the Anterior Glenoid Rim

Abstract: Recurrent anterior shoulder instability is associated with glenohumeral bone loss. Glenoid deficiency compromises the concavity-compression mechanism. Medial Hill-Sachs lesions can result in an off-track humeral position. Anterior glenoid reconstruction or augmentation prevents recurrence by addressing the pathomechanics. In Bristow and Latarjet procedures, the coracoid process is harvested for conjoint tendon transfer, capsular reinforcement, and glenoid rim restoration. Complications and the nonanatomic natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 61 publications
0
34
0
4
Order By: Relevance
“…Although the iliac crest is a convenient source of customizable autologous bone grafts, it has been associated with a substantial risk of chronic degenerative changes in the glenohumeral joint as well as immediate and, sometimes, persistent pain at the donor site [35,36]. Allogeneic osteochondral iliac crest grafts were introduced to minimize the risk of arthropathy and donor site morbidity [18]. Although concerns have been raised regarding potential early resorption and inadequate osseointegration of the graft, an allograft-focused review showed that allograft reconstruction for glenoid bone loss provided excellent clinical outcomes, low rates of recurrent instability, and high osseous incorporation rates with no evidence of graft resorption [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the iliac crest is a convenient source of customizable autologous bone grafts, it has been associated with a substantial risk of chronic degenerative changes in the glenohumeral joint as well as immediate and, sometimes, persistent pain at the donor site [35,36]. Allogeneic osteochondral iliac crest grafts were introduced to minimize the risk of arthropathy and donor site morbidity [18]. Although concerns have been raised regarding potential early resorption and inadequate osseointegration of the graft, an allograft-focused review showed that allograft reconstruction for glenoid bone loss provided excellent clinical outcomes, low rates of recurrent instability, and high osseous incorporation rates with no evidence of graft resorption [37].…”
Section: Discussionmentioning
confidence: 99%
“…The initial procedure which has a 100-year history was based on the concepts of anatomic glenoid bony augmentation with a tibial autograft and capsulorrhaphy [17]. The traditional glenoid reconstruction has historically been associated with increased risk of postoperative degenerative changes [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the results published with the Latarjet procedure in athletes are encouraging, there is concern over the potential complications associated with these nonanatomic procedures 14, 15, 16. The most common complications include infection, frozen shoulder, hematoma formation, symptomatic implants, fracture or nonunion of the coracoid graft, neurologic complications, arthritis, and recurrence of instability 16, 17. However, a large recent review reported an overall complication rate in the open Latarjet procedure of 15%, with 7% of patients requiring an unplanned reoperation following surgery 6 …”
Section: Discussionmentioning
confidence: 99%
“…With an incidence of 23.9/100,000 person-years, anterior shoulder instability is a common problem [3]. Several aspects in the management of anterior shoulder instability continue to be controversial with a lack of consensus on treatment protocols especially in the face of glenoid and/or humeral head bone loss [4].…”
Section: Introductionmentioning
confidence: 99%
“…The current indications for open coracoid transfer are controversial; the procedure is usually reserved for cases with GBL more than 20-30% although some European centres use the technique for GBL as low as 10% [4]. Recent comparative studies indicate that primary Latarjet has a reduced risk of recurrence compared to arthroscopic Bankart repair [14,15].…”
Section: Introductionmentioning
confidence: 99%